Kerugian Ekonomi Akibat Penyakit Rabies di Provinsi Nusa Tenggara Timur (ECONOMICAL LOSSES OF RABIES DISEASE IN EAST NUSA TENGGARA PROVINCE) - Wera, Ewaldus; Geong, Maria; Sanam, Maxs Urias Ebenhaizar (Jurnal Veteriner, 2013)
The objective of this paper was to analyze economic impact of rabies in East Nusa Tenggara Province.Data from Health Department of East Nusa Tenggara Province (Period 1998-2007) were applied to a setof link the economics model. Analysis presented in this paper only costs related with PET, Vaccination andelimination of dogs. The total societal cost (PET in human) incurred by the disease was about Rp 19.9billion. The cost included transport cost to and from rabies-treatment centers, and loss of income whilereceiving treatment. The cost of vaccination was estimate about Rp 50.000 per dog and about 140.000dogs were vaccinated per year in the area. For this analysis, vaccination costs per dog included relatedcomponents on campaign organization, public awareness efforts, transport and biological and materialcosts. The economic losses due to the culling and vaccination program in dogs wes about Rp 5,3 and Rp 7billion per year, respectively. Total cost for vaccination and elimination of dog from 1998 through 2007 wasabout Rp 122,5 billion or Rp 12,3 billion per year. Total economic lost due to rabies in East Nusa TenggaraProvince during 1998-2007 was approximately 14,2 per year. The economic losses may be reduced byoptimalisation of rabies control in animal reservoir of rabies especially in dogs. The elimination of rabiesin dogs through mass vaccination with minimal coverage 70% of dog population is believed contribute tominimise rabies in human.
Keywords: Rabies, Economic Losses, East Nusa Tenggara Province